Pengaruh rasio doxorubisin: Apoferritin terhadap kapasitas dan efisiensi enkapsulasi doksorubisin dalam apoferritin - Novita Wiwoho; Maria Christina P.; Mujamilah; Grace Tj. Sulungbudi (Jurnal Rekayasa Proses, 2017)
Doxorubicin is a chemotherapy drug which is very toxic and causes many side effects. To reduce side effects, doxorubicin can be encapsulated by apoferritin into apoferritin doxorubicin (Apo-Dox) system. In this research, various mass of doxorubicin i.e. 0.17 mg (S1), 0.26 mg (S2), 0.35 mg (S3), and 0.52 mg (S4) were encapsulated with 21.50 mg apoferritin. Encapsulation process was carried out by lowering pH medium for apoferritin dis-assembly, doxorubicin addition and dialysis for gradual and controlled pH-increase of medium to support re-assembly of apoferritin and doxorubicin encapsulation. End-result samples were then centrifuged and washed to separate the unreacted doxorubicin and apoferritin’s subunits. Doxorubicin encapsulation efficiency was determined using microplate reader spectrophotometry. The highest encapsulation capasity was 3.87 g dox/mg apo for S4 samples. Increasing the weight of doxorubicin gives more significant effect on increasing the reactive weight of apoferritin, which reached 93.73% (S4 sample). Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) analysis confirm that apoferritin is in the Apo-Dox sample.